2020
DOI: 10.1016/j.puhe.2019.11.008
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic inequalities and the equity impact of population-level interventions for adolescent health: an overview of systematic reviews

Abstract: Socioeconomic inequalities and the equity impact of population-level interventions for adolescent health: An overview of systematic reviews ABSTRACTObjectives: Despite robust evidence on health inequalities in adulthood, less attention has been paid to inequalities in adolescence. The aim of this overview was to examine systematic review (SR) evidence on the equity impact of population-level interventions intended to improve health, happiness and wellbeing for adolescents.Study Design: An overview (review of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 73 publications
(129 reference statements)
1
10
0
3
Order By: Relevance
“…We screened titles and abstracts of 1145 studies and included 16 published umbrella reviews [ [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] ]. Nineteen grey literature reports [ [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] ], 12 systematic reviews [ [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] ], and 3 primary studies [ [62] , [63] , [64] ] were also included (see Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We screened titles and abstracts of 1145 studies and included 16 published umbrella reviews [ [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] ]. Nineteen grey literature reports [ [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] ], 12 systematic reviews [ [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] ], and 3 primary studies [ [62] , [63] , [64] ] were also included (see Fig.…”
Section: Resultsmentioning
confidence: 99%
“… 11 of 17 studies on contractionary policies (decreased benefit amount or access) worsened mental health; 10 evaluated inequalities which widened in 3, narrowed in 2, and had mixed or no effects in 5. Macintyre (2020) [ 21 ] 15 SRs (1720 studies) Adolescent health Evidence for market regulation impact in SR on youth smoking found 7 (of 38) studies showed positive impact on inequalities, 16 showed neutral effects, 12 negative impact, 4 mixed and 1 unclear. Taxation/increasing the price of cigarettes had the most evidence for positive equity impact.…”
Section: Resultsmentioning
confidence: 99%
“…verse ment rĂ©gulier de sommes d'argent aux personnes ou aux mĂ©nages), car de nou velles donnĂ©es ont fait la preuve de leurs effets positifs sur la santĂ© 52 . Les interven tions fondĂ©es sur une approche intersecto rielle qui visent les milieux sociaux, Ă©conomiques et physiques se sont rĂ©vĂ© lĂ©es efficaces chez les adultes 53 , mais des donnĂ©es supplĂ©mentaires sont nĂ©cessaires sur les interventions efficaces Ă  l'Ă©chelle de la population qui s'attaquent aux inĂ© galitĂ©s socioĂ©conomiques chez les adolescents 54 .…”
Section: Garçons Fillesunclassified
“…Therefore, investing in the reduction of socioeconomic inequalities in children is of utmost importance ( Marmot & Bell, 2019 ). Although much research has been performed on the magnitude and causes of socioeconomic inequalities, relatively less is available on effective approaches to reduce them ( Macintyre et al, 2020 ; Marmot & Bell, 2019 ).…”
Section: Introductionmentioning
confidence: 99%